Pengaruh Perputaran Persediaan, Perputaran Modal Kerja, Perputaran Kas Terhadap Profitabilitas Pada Perusahaan Sub Sektor Kosmetik dan Barang Keperluan Rumah Tangga Yang Terdaftar di BEI Tahun 2019-2023 - Zeva Anela Nababan; Siti Aisyah (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the effect of auditor reputation and firm size on audit delay in manufacturing companies listed on the Indonesia Stock Exchange. Audit delay refers to the time lag between the fiscal year-end and the audit report date, which is crucial for the timeliness of financial information. This research applies a quantitative method with the population of all manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2023 period. The sample was determined using purposive sampling, resulting in 30 companies. The data used were annual financial reports, and the analytical technique employed was multiple linear regression with the SPSS program. The results indicate that auditor reputation significantly influences the timeliness of audit completion, while firm size has no significant effect on audit delay. These findings are expected to provide insights for companies, auditors, and future researchers regarding the determinants of audit delay.